Jeavons syndrome - clinical spectrum, diagnostic challenges and innovative treatment strategies - Martyna Borowska-Łygan; Patrycja Grzech; Lena Maria Kreczyńska; Aleksandra Banach; Weronika Emilia Zubrzycka; Patryk Harnicki; Weronika Ożóg; Klaudia Piskorowska (Journal of Education, Health and Sport)
Introduction: Jeavons syndrome (JS), also known as epilepsy with eyelid myoclonus (EEM), is a rare form of genetically generalized epilepsy (GGE) characterized by light-triggered seizures, eyelid myoclonus, and often concurrent absence seizures and GTCS. The condition is sometimes misdiagnosed as neural tics, leading to significant diagnostic delays. In recent years, there has been growing interest in new treatments for JS, including alternative approaches in cases of treatment resistance. Objective: The purpose of this study is to provide an update on Jeavons syndrome, including clinical presentation, genetic factors, diagnostic methods and the latest therapeutic strategies. Methods: A non-systematic review of the scientific literature from 2020-2025 was performed using PubMed, Google Scholar, Web of Science and Scopus databases. Publications describing JS, treatment of drug-resistant epilepsy, eyelid myoclonus, dietary therapy and modern brain stimulation methods were included. Results: